RESEARCH GROUPS IN MATHEMATICS EDUCATION AS AN OBJECT OF STUDY: A VIEW OF THE STATE OF ART - Alves, Carlos Alex [UNESP]; da Silva, Leandro Londero [UNESP] (FapUNIFESP (SciELO), 2023)
This article presents a state of the art about research groups in mathematics education as an object of study. We analyzed a set of 25 papers validated in a survey at the Brazilian Digital Library of Theses and Dissertations and Google Scholar, elucidating their authors, titles, themes, areas of investigation and methodological approaches. The main results evidenced the presence of articles published in periodicals, by the Oral History and Mathematics Education Research Group, and works that analyze/describe aspects of trajectory, constitution, identity, scientific habitus, functioning, collaboration and/or scientific production of the research groups. We argue that future research may privilege the magnitude of research groups in mathematics education in Brazil.
LOS GRUPOS DE INVESTIGACIÓN EN EDUCACIÓN MATEMÁTICA COMO OBJETO DE ESTUDIO: UNA VISIÓN DEL ESTADO DEL ARTE
GROUPES DE RECHERCHE SUR L’ENSEIGNEMENT DES MATHÉMATIQUES EN TANT QU’OBJET D’ÉTUDE: UNE VISION DE L’ÉTAT DE L’ART
Keywords: MATHEMATICS EDUCATION; RESEARCH GROUPS; STATE OF ART